Cloud computing : Principles and paradigms - Buyya, Rajkumar (John Wiley & Sons, 2011)
Contents: Introduction to Cloud Computing; migrating into a Cloud; enriching the 'Integration as a Service' paradigm; the enterprise cloud computing paradigm; virtual machines provisioning and migration services;...